Sistem Akuntansi Manajemen Keuangan Terintegrasi E-Commerce Untuk Meningkatkan Akurasi Laporan Keuangan Ewilla Sewing Demak - Sukemi Kamto Sudibyo; Eni Endaryati; Vivi Kumalasari Subroto; Sri Wahyuning; Nur Rokhman; Agus Priyadi; Delinda Dalis Yuliani (MANAJEMEN, 2025)
The development of digital technology encourages business entities to utilize e-commerce to expand their market. However, many have difficulty managing financial reports because the online sales system is not yet integrated. Ewilla Sewing, a convection business, still records finances manually and separately from online sales.  This study designs and implements an integrated e-commerce financial management accounting system to improve the accuracy, efficiency, and reliability of financial reports. The research method uses a descriptive qualitative approach with observation, interviews, and document analysis. The system was developed with a waterfall model. The results of the study show that the system is able to manage finances more efficiently, accelerate reporting, provide real-time data, support internal audits, and help make more appropriate decisions for Ewilla Sewing.